Sebuah Karakteristik dari Modul Uniserial dan Gelanggang Uniserial - I Gede Adhitya Wisnu Wisnu Wardhana; Fariz Maulana (Unisda Journal of Mathematics and Computer Science (UJMC), 2021)
The module is a generalization of the vector space. The module that will be discussed is a uniserial module, which is a module that only has one composition series. A uniserial ring is a ring whose module over itself is uniserial. The uniserial ring is an Artin and local ring, but the converse is not necessarily true. In this paper, we will discuss Artin and local ring with additional properties so that it is characteristics of the uniserial ring.